PENGARUH FLUKTUASI MUKA AIR RESERVOIR TERHADAP STABILITAS BENDUNGAN TANAH (UJI MODEL FISIK DI LABORATORIUM) - , MAIMUNAH,ST ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Many failures in earthdam construction caused by extremes of level fluctuation in reservoir. Earthdam construction failures can be avoided if dam slope are in stable condition. This research discusses about the The effect of reservoir level fluctuation on the stability of earth dammodel in laboratory by analyzing stresses and deformation using Plaxis Program version 8.2. Implementation of the research done in stages which include testingproperties of the building blocks of the model earth dam and physical modeling experiments with three (3) variations in soil types, namely: a mixture of90% sand-silt10%, and80% sand mixture-silt20% and100% soil. The slope ofthe model on the upstream side 1:1 and 1:1.5, while in the downstream dam slope was maintained constantat 1:1. Instrumentationused includes 6 soil moisture sensors with an accuracy of2%, 1 deformation pressure sensor with detection range, 3dial gauge, capacity level meterwith accuracy2%. Furthermore analysis on the stability of the earth dam model experiment using Plaxis program version 8.2. The results of this Plaxis analysis in the form of total displacement, total stress, total strain, pore water pressure and the safe rate (safety factor). Based on the review of the three nodal models in the upstream slope of the dam are same, the effective value of the largest stresses occur in the model 10% soil 90% sand with the upstream slope 1: 1, that is equal to -16.52 kN / m 2 in Lowering phase.For a total value of largest stresses occur in the model 20% soil 80% sand with the upstream slope 1: 1, that is equal to -12.89 kN / m 2 in Rising 3 phase .Displacement (vertical displacements, the total displacements, the total incremental displacements and incremental strains) , the largest value occurs in the model 100% of the land, the vertical displacements 8,12.10-6 m, the total large displacements 3,92.10-5 m, m 1,43.10-5 total incremental displacements and incremental strains for-1,75.10-2 %. Lowest safety factor (critical condition) due to raising and lowering of water level in the upstream occurred at a slope 1: 1 at 1.4710.